Experimental and numerical investigations on the microstructural features and mechanical properties of explosive welded niobium-steel interface - Junfeng Xu; Honghao Ma; Ming Yang; Zhaowu Shen; Bingyuan Zhang; Tianan Rui; Ruijin Zhao (Materials & Design, 2022)
The microstructural characteristics of the explosive welded niobium-steel interface were systematically investigated by various characterizations and a two-step numerical simulation. A coupled Lagrange-Eulerian simulation was firstly developed to compute the impact velocity, this model allows to establish an accurate impact condition. Microstructure observations show that the niobium-steel interface is featured by a wave structure with two vortices located at the wave front and back, and micro defects like voids and cracks were detected inside the vortex. Grains of the niobium and steel matrix near the interface were characterized by elongated and fine equiaxed structures, respectively, while that in vortex area was fine columnar grains. Then, the interfacial thermokinetics was investigated by a smoothed particles hydrodynamics simulation to reveal the formation of the observed defects and diverse grains. The ultimate strength of the composite exceeds 350 MPa with disparate heat-treated temperatures obtained by the tensile tests. Meanwhile, tensile-shear test shows a robust bonding strength of 220 MPa. The strong mechanical properties of the composite guarantee a great prospect of its application in the nuclear industry.